ANALISIS TINGKAT KINERJA GURU TETAP YAYASAN (GTY) DAN GURU TIDAK TETAP (GTT) DI SMK SWASTA SE-KOTA MALANG - Moch Sheisar Firmana (Ma Chung Press, 2018)
Teachers are educators who are serving the school and teaching students. There are two statuses of teachers, permanent and non-permanent teachers. There is a problem research, which there any differences between the permanent teachers with the non-permanent teachers on Private Vocational High School in Malang City. The purpose of this research to identify and analyze differences in job performance level of permanent teachers and non-permanent teachers at The Private Vocational High School (SMK) in Malang City. The populations of this research are all Private SMK in Malang, which are amount 40 schools. The sample of this research are 10 schools, each school will be represented by 5 permanent teachers and 5 non-permanent teachers and the amount of all samples will be 50 permanent teachers and 50 non-permanent teachers. This research is using questionnaire and interview data gathering. The data analysis uses Chi-square statistic technique. The result shows that there is no difference between permanent teachers and non-permanent teachers job performance at The Private SMK in Malang City.